Consequences of visiting restrictions during the COVID‐19 pandemic: An integrative review. (September 2021) - Hugelius, Karin; Harada, Nahoko; Marutani, Miki
Abstract: Background: During the COVID-19 pandemic, visiting restrictions of different extents have been implemented. However, despite the long history of visiting restrictions in health care systems, little is known about their effects. Objectives: This review sought to explore the consequences of visitor restrictions in health care services during the COVID-19 pandemic. Methods: A systematic, integrative review was conducted in accordance with the PRISMA guidelines, based on a systematic search in PubMed, CHINAL full plus, Web of Science, PsychInfo, Scopus and the Cochrane Library. Results: A total of 17 scientific papers covering intensive care, pediatric care, general medical care, hospital care, palliative care and nursing home settings were included. Although appreciation for the technical solutions enabling remote meetings was reported, visiting restrictions had several consequences, mainly negative, for the patient's health, the health and wellbeing of family members and the provision of care. Among physical health consequences, reduced nutrition intake, decreased activities of daily living and increased physical pain and symptoms were reported. Among mental health consequences for the patient, loneliness, depressive symptoms, agitation, aggression, reduced cognitive ability and overall dissatisfaction were observed. For family members, worry, anxiety and uncertainty occurred, and they reported an increased need for information from care providers. Family members of neonatal intensive care unit patients reported less bonding with their child and family relation disturbances due to the restrictions. For care providers, visiting restrictions added the burdens of ethical dilemmas, learning new technical means to enable social interaction and an increased demand for communication with families and providing social support to both family members and patients. Conclusions: When implementing visiting restrictions in health care services, decision makers and nurses need to be aware of their potential negative effects and adapt the provision of care to compensate for such effects. Nurses in all sectors should be aware that visiting restrictions may affect patients, families, and health care services for longer than the actual pandemic. Since the level of evidence regarding effect from visiting restrictions is low, further studies is strongly needed.